Calibration model for detection of potential demodulating behaviour in biological media exposed to RF energy. Issue 7 (1st October 2017) - See, Chan H.; Abd‐Alhameed, Raed A.; Ghani, Arfan; Ali, Nazar T.; Excell, Peter S.; McEwan, Neil J.; Balzano, Quirino
Abstract : Potential demodulating ability in biological tissue exposed to radio‐frequency (RF) signals intrinsically requires an unsymmetrical diode‐like non‐linear response in tissue samples. This may be investigated by observing possible generation of the second harmonic in a cavity resonator designed to have fundamental and second harmonic resonant frequencies with collocated antinodes. Such a response would be of interest as being a mechanism that could enable demodulation of information‐carrying waveforms having modulating frequencies in ranges that could interfere with cellular processes. Previous studies have developed an experimental system to test for such responses: the present study reports a circuit model to facilitate calibration of any non‐linear RF energy conversion occurring within a test‐piece inside the cavity. The method is validated computationally and experimentally using a well‐characterised non‐linear device. The proposed model demonstrates that the sensitivity of the measurement equipment plays a vital role in deciding the required input power to detect any second harmonic signal, which is expected to be very weak. The model developed here provides a lookup table giving the level of the second harmonic signal in the detector as a function of the input power applied in a measurement. Experimental results are in good agreement with the simulated results.